TIPS MEMBUAT CV ATS FRIENDLY - Retno Setya Budiasningrum; Rahmi Rosita; Jajang Setiawan; Dyan Yuliana; Enny Diah Astuti (JURNAL ABDIMAS PLJ, 2022)
Curriculum vitae is the most important thing when applying for a job, but unfortunately, most applicants cannot win the attention of the recruiters because their profile is too simple. Applicants should tell more about themselves, especially their abilities to pursue the recruiters’ attention. Conducting the training may help the students of PKBMN 23 Jakarta create a curriculum vitae that ATS friendly. By giving them training, hopefully, the participants will be able to create a good curriculum vitae ATS friendly and pass the screening by the ATS software.Keywords: CV, Tips, ATS Friendly